Combined Line Fault Location Method for MMC–HVDC Transmission Systems - Qing Huai; Liang Qin; Kaipei Liu; Hua Ding; Xiaobing Liao; Tianyuan Tan (IEEE Access, 2020)
A combined algorithm based on traveling wave (TW) theory and time-frequency characteristics is proposed to estimate the DC line fault location in modular multilevel converter-high voltage direct current (MMC-HVDC) systems. The relationship between instantaneous frequency and TW propagation velocity is analysed, and the local voltage signal is utilized to extract fault features. A TW distortion-based scheme is improved to obtain the approximate fault location and accurately detect TW arrival times. The arrival times of the initial TW from the fault point and opposite terminal are determined using intrinsic mode functions under variational mode decomposition. Given the attenuation property of the TW-based method, the Teager energy operator is used to overcome the weakness in fault feature extraction. The instantaneous frequency of the TW front is obtained via ensemble empirical mode decomposition and Hilbert-Huang transform. The fault location is predicted with the detected TW arrival times and corresponding TW propagation velocity. The effectiveness and superiority of this method are verified through simulations in PSCAD/EMTDC and computation in MATLAB.